INFORMATION TECHNOLOGIES IN EDUCATION (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
In today's digital age, information technologies (IT) have become indispensable tools in reshaping the landscape of education. The integration of IT in education has led to significant advancements, offering unprecedented opportunities for teaching and learning. This article embarks on a comprehensive review and analysis of the integration of IT in education, aiming to provide insights into its impact, challenges, and future prospects. Through the structured approach of the IMRAD framework, this paper explores the multifaceted relationship between IT and education, delineating key aspects such as e-learning, educational software, and virtual classrooms. By examining these facets, this study endeavors to unravel the transformative potential of IT in shaping the future of education.